PENAMPILAN SEPULUH VARIETAS KEDELAI YANG DITUMPANGSARIKAN DENGAN TEBU - Iskandar Umarie; M. Hazmi; Oktarina Oktarina (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2018)
[PERFORMANCES OF TEN SOYBEAN VARIETIES AS INTERCROPPED WITH SUGARCANE]. An intercropping system between soybean and sugarcane may be an alternative to increase soybean production in Indonesia, but not all soybean varieties are suitable for intercropping system as different soybean varieties may perform differently under intercropping system and monoculture system. Therefore, suitable soybean varieties for intercropping should be identified to warrant the higher crop productivity. This study was conducted to to compare the growth and yield performances of ten soybean varieties in monoculture and soybean-sugarcane intercropping systems. The experiment was laid in a Split Plot Design with three replications. The cropping systems (monoculture and intercrop) were allotted in the main plots, while the soybean varieties (Gepak Kuning, Kaba, Wilis, Tanggamus, Burarang, Sinabung, Anjasmoro, Agromulyo, Ring-1, and Gema) were assigned as the sub plots and allotted randomly in each main plot. On overall, the intercropping system had significantly reduced the soybean pod number, seed number, wight of 100 seed, and, seed yield/plant, but increased plant height as compared to the monoculture system. The exceptions were observed for seed number and weight of 100 seed. The reduction of seed number was not significant on Agromulyo and Dering-1.On the other hand, Anjasmoro and Dering-1were the only varieties showed significant reduction in weight of 100 seed. Kaba, Willis, Tanggamus, Burarang, Sinabung, and Dering-1 showed their consistant performormances across the cropping systems. However, the higher seed yield/plant in both systems was observed on Gepak Kuning, Willis, Burarang, Agromulyo, Dering-1, and Gema.